Zuwanderung in Städte: Chancen und Grenzen der planerischen Steuerung - Manfred Kühn (disP - The Planning Review, 2021)
In-migration is a key factor in the growth of cities and an indicator of their attractiveness in the competition between locations. This article investigates the central question of which approaches for the proactive recruitment of in-migrants arise in urban planning and which opportunities and obstacles exist for local governance. On the basis of planning-related theories, a heuristic model for the analysis of local strategies is developed that differentiates in-migration on the housing, labour and education markets. In the empirical part, selected results from qualitative case studies in medium-sized cities are presented. The results show that, in the context of shrinking cities, there is a need for in-migration due to vacant apartments and a shortage of skilled workers, while in the growth context, the problems of a tight housing market as a result of migration move to the fore of city policies. Strategies to attract in-migration are therefore context-dependent and represent a complex cross-sectional task that requires the planning administration to interact with politicians, business and citizens. While growth coalitions are being formed in some cities, in other cases there are barriers that block the development of local in-migration strategies.
Keywords: 710